Biological aspects of sharks caught off the Coast of Pernambuco, Northeast Brazil - AF. Fischer; FHV. Hazin; F. Carvalho; DL. Viana; MG. Rêgo; C. Wor (Brazilian Journal of Biology)
One hundred seventeen specimens of sharks were caught along the coast of Pernambuco State, Northern Brazil, between May 2004 and May 2007, among which 86 were blacknose sharks, Carcharhinus acronotus, enabling a more detailed study of the species. Blacknose sharks were caught in the 2 study areas along the Boa Viagem/Piedade and Paiva beaches, accounting for the highest relative abundance among the species caught (73.5% of total). Potentially dangerous sharks, tiger and bull sharks, were also caught in the same areas, whereas hammerhead and blacktip sharks were only captured off Boa Viagem/Piedade. Concerning the blacknose shark, the total length (TL) ranged from 39.0 to 180.0 cm. Among the 38 females analysed, 32 were juveniles, 11 were maturing, 2 were pre-ovulatory and 21 were pregnant. Sexing was possible for 75 of the 83 embryos, 38 of which were males and 37 were females, with a sex proportion of 1:0.9 and total length ranging between 6.4 and 63.5 cm. Ovarian fecundity ranged from 5 to 10 and uterine fecundity from 1 to 3, with an estimated gestational period of 9 months. Among the 48 males, 6 were juveniles and 42 were adults. Both males and females seem to reach sexual maturity at about 105.0 cm TL. Among the 86 stomachs analysed, only 22.1% had contents, with teleosts as the most frequent item.